Analisis Butir Soal Buku Siswa Mata Pelajaran Bahasa Indonesia Kelas V Dari Komponen Literasi Membaca - Putri, Lesti Dwi; Lusa, Herman; Amaliyah, Yuli (JURIDIKDAS, 2025)
This research aims to determine the quality of the questions in the fifth grade Indonesian language student handbook in terms of the comp.onent.s o.f t.e.xt content, text co.nte.xt a.n.d c.og.nitive l.ev.el. The researcher used qualitative research with a qualitative descriptive method and the subject used in this research was the student handbook for the Indonesian Language Moving Together subject of the class V independence curriculum with the help of a document analysis sheet in the form of a student handbook for the class V Indonesian Language subject and appropriate documents/literature with a research focus. This research uses data collection techniques in the form of observation and documentation, data is analyzed using data collection, data reduction, data display and conclusion drawing/verification. The research results show that the most dominant content components are informational texts (58.4%), and fictional texts (41.5%). The most dominant context components are personal (71.1%), socio-cultural and scientific (14.4%). The most dominant cognitive level components are finding information (87.7%), interpreting and integrating (7.7%), evaluating and reflecting (4.4%)